Image1.TIF - Mark J. Hopwood; Ulf Riebesell; Javier Arístegui; Andrea Ludwig; Eric P. Achterberg; Nauzet Hernández (2018)
In the surface ocean, microorganisms are both a source of extracellular H 2 O 2 and, via the production of H 2 O 2 destroying enzymes, also one of the main H 2 O 2 sinks. Within microbial communities, H 2 O 2 sources and sinks may be unevenly distributed and thus microbial community structure could influence ambient extracellular H 2 O 2 concentrations. Yet the biogeochemical cycling of H 2 O 2 and other reactive oxygen species (ROS) is rarely investigated at the community level. Here, we present a time series of H 2 O 2 concentrations during a 28-day mesocosm experiment where a pCO 2 gradient (400–1,450 μatm) was applied to subtropical North Atlantic waters. Pronounced changes in H 2 O 2 concentration were observed over the duration of the experiment. Initially H 2 O 2 concentrations in all mesocosms were strongly correlated with surface H 2 O 2 concentrations in ambient seawaters outside the mesocosms which ranged from 20 to 92 nM over the experiment duration (Spearman Rank Coefficients 0.79–0.93, p-values < 0.001–0.015). After approximately 9 days of incubation however, H 2 O 2 concentrations had increased across all mesocosms, later reaching >300 nM in some mesocosms (2–6 fold higher than ambient seawaters). The correlation with ambient H 2 O 2 was then no longer significant (p > 0.05) in all treatments. Furthermore, changes in H 2 O 2 could not be correlated with inter-day changes in integrated irradiance. Yet H 2 O 2 concentrations in most mesocosms were inversely correlated with bacterial abundance (negative Spearman Rank Coefficients ranging 0.59–0.94, p-values < 0.001–0.03). Our results therefore suggest that ambient H 2 O 2 concentration can be influenced by microbial community structure with shifts toward high bacterial abundance correlated with low extracellular H 2 O 2 concentrations. We also infer that the nature of mesocosm experiment design, i.e., the enclosure of water within open containers at the ocean surface, can strongly influence extracellular H 2 O 2 concentrations. This has ...